Evaluation of the Impact of Increasing Population Density Against Water Resources in Coastal Areas - Fenia Hayatun Nikmah; Ade Jaya Saputra (LEADER: Civil Engineering and Architecture Journal, 2023)
study states that there are about 16% of coastal areas whose conditions are still relatively good. Most of the coastal areas on earth have been badly damaged and it is impossible to return to normal. Research on evaluating the impact of coastal development and coastal resources uses literature research methods, especially journals that can be accessed online from both Indonesian and foreign journals. Regarding spatial planning of the country's territory, it is regulated in Law no. 24/1992 concerning Spatial Planning. In his explanation it was stated that the territory of the Unitary State of the Republic of Indonesia is the entire territory of the country including land, sea and air based on applicable laws and regulations, including the sea and the surrounding continental shelf. This study aims to evaluate by analyzing data and influencing factors related to the impact of increasing population density on water resources in coastal areas. The perspective that can be used is a combination perspective, which holds that there are a number of root causes of environmental degradation that play a role in a particular area. So that the residential environment which is also not good becomes an important thing to arrange due to population density.